Management Analysis Of The Premarital Counseling and Health Screening Program In Kediri - Anna Trisna Wati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Maternal mortality during pregnancy, childbirth and puerperium fase is an evaluation of maternal health status before pregnancy. The period of preparation for marriage is the right time to do a thorough preparation in physical health, psychological and social health. The purpose of this study was to determine the function of the management of premarital counseling and health screening program in Kediri. The research design is a qualitative research with a case study approach. Data collection using in-depth interview techniques with semi-structured questions with 21 informants. From the research result shows that the premarital counseling and health screening program in Kediri include four aspects of management functions, namely planning, organizing, implementing and evaluating. In the planning process it has not been implemented optimally because this program is still new and a top down program implemented under SE Mayor No. 441.7 / 7178 / 419.108 / 2017 so the process of analyzing the program situation specifically must be done more optimally. In the function of organizing the premarital program, it does not have a formal team, inter professional collaboration is carried out according to its authority so that the sense of ownership of the program is not yet strong in program implementers. In the implementation function, this program is an individual health effort of the Public Health Center with clear service flow and administrative system, coordinating with the stakeholders. The assessment function must optimize in monitoring, supervision and appreciation so that it becomes the leverage force for the achievement of program objectives